Healthy Child Food Motorbike Taxi Program (OMAS) to Prevent Stunting in Sungai Pinang Village - Firmanda, Hengki; Hasyim, Kabul; Ismail, Hilmi; Cantika, Rancy; Nainggolan, Juan Piaz; Sahara, Elpi; Darlusi, Nindia Putri; Hasanah, Hasanah (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The primary aim of this study was to address the issue of stunting, a form of chronic malnutrition affecting children’s growth and development. This problem is influenced by various factors, including child characteristics and socio-economic conditions. The lack of knowledge about stunting among village residents necessitated an intervention to provide insight and education. Method: Students from Riau University’s KKN program collaborated with the Sungai Pinang Village Posyandu to conduct stunting prevention outreach activities. These activities were designed to educate parents, particularly mothers, about the importance of adopting a healthy and clean lifestyle. In addition to these outreach activities, the students implemented a program called “Motorbike Taxi for Healthy Children’s Food”. This program aimed to provide examples of nutritionally balanced food menus beneficial for children’s growth and development. Practical Applications: The practical application of this study lies in its potential to increase community awareness about stunting prevention and healthy food menus. By providing practical examples and education, the residents of the village can make informed decisions about their children’s nutrition. Conclusion: The desired outcome of these activities is a community that has sufficient knowledge about stunting prevention and healthy food menus. The hope is that village residents will no longer feel unfamiliar with the concept of stunting and will know how to prevent it. Furthermore, they will be able to provide healthy food for their children, contributing to the overall reduction of stunting in the community.